Mini Audit Communication of Muhammadiyah Student Association : Audit Mini Komunikasi Anggota Ikatan Mahasiswa Muhammadiyah - Muhammad Faishal Azami; Ainur Rochmaniah (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to describe how the implementation of a communication mini audit of members of the Muhammadiyah Student Association (Case Study on IMM Korkom Umsida). This research uses quantitative descriptive research. Researchers use this type of research to determine the organizational communication process in IMM Korkom UMSIDA. The results of this study indicate that the Muhammadiyah Student Association (IMM) has good communication with fellow members and with leaders. This includes aspects of management, organization, and communication to IMM members with good procedures for managing members or organizations and their communications. While in the aspect of feedback with a value of 61% and although the lowest, this aspect is still in the good category. To support and enrich the development of knowledge, especially regarding the mini-audit of communication of members of the Muhammadiyah Student Association.